Preparation and application of NiAl2O4-loaded Ni2P dehydrogenation catalyst
By using Ni2P/NiAl2O4 dehydrogenation catalyst of Ni2P/NiAl2O4 in the synthesis of benzofuran-2(3H)-one, environmental pollution, low yield and precious metal catalysts in the prior art are solved by using Ni2P spinel support and Ni2P active components. The problem of poor stability achieves an efficient and low-cost catalytic effect.
Patent Information
- Application Number
- CN202310706807.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, when synthesizing benzofuran-2(3H)-one, the use of highly corrosive liquid acids leads to environmental pollution, harsh reaction conditions, low yield, and high cost of precious metal catalysts and easy to accumulate carbon, and poor stability.
Ni2P/NiAl2O4 dehydrogenation catalyst with Ni2P as the carrier and transition metal phosphide Ni2P as the active component is used. The catalyst is prepared by combining nickel and aluminum salt into a mixed solution, precipitation and calcination, and alkaline such as NaOH and Na2CO3. The precipitant is used to form a nickel-aluminum spinel carrier, and then react with the phosphorus salt to form the active Ni2P component, which is used for the dehydrogenation reaction of 7,7a-dihydro-2(6H)-benzofuranone.
It improves the stability of the catalyst and the resistance to carbon deposits, reduces production costs, improves the reaction activity and selectivity, ensures high conversion and selectivity, and reduces environmental pollution.
Smart Images

Figure CN119140131A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a preparation method and application of a Ni2P / NiAl2O4 dehydrogenation catalyst, wherein 7,7a-dihydro-2(6H)-benzofuranone is used as a raw material to obtain benzofuran-2(3H)-one through catalytic dehydrogenation. Background Art
[0002] Benzofuran-2(3H)-one, English name 2-Coumaranone, alias benzofuranone, 2-coumaranone, molecular formula C8H6O2, pure product is light yellow or brown powder, melting point 49-51℃, boiling point 248-250℃, relative density 1.22. Uses: Benzofuran-2(3H)-one has good physiological activity, can be used to synthesize medicines, pesticides and new antioxidants, and is also an important raw material for synthesizing fungicides azoxystrobin, with the characteristics of high efficiency, low toxicity and broad spectrum.
[0003] At present, the following methods are mainly used for synthesis at home and abroad: (1) using o-hydroxyphenylacetic acid as a raw material and p-toluenesulfonic acid as a catalyst to obtain benzofuran-2(3H)-one through dehydration (World Patent WO92 / 08703); (2) using o-chloro, o-bromo or o-iodophenylacetic acid as a raw material, after high temperature, high pressure and strong base reaction, it is then acidified to form o-hydroxyphenylacetic acid, and then benzofuran-2(3H)-one is obtained under microwave-enhanced conditions (Chinese Patent CN201210393538.4); (3) using o-hydroxyacetophenone as a raw material, thiophenylacetamide is obtained under the action of morpholine, and then o-hydroxyphenylacetic acid is hydrolyzed to obtain o-hydroxyphenylacetic acid, and then intramolecular esterification is carried out under the catalysis of toluenesulfonic acid to obtain benzofuran-2(3H)-one (Chinese Patent CN201911340181.1). In the above methods, highly corrosive liquid acid is used in the reaction process, resulting in large equipment investment. The acid dissolved in the product needs to be treated with a large amount of water, which causes great pollution to the environment. In addition, the traditional synthesis method is to obtain the corresponding o-hydroxyphenylacetic acid by catalysis with an acid catalyst. Since the preparation route of o-hydroxyphenylacetic acid is long, the reaction conditions are harsh, the yield is not high, and the production cost is increased.
[0004] Using dihydroxyacetic acid (glyoxylic acid) and cyclohexanone as raw materials, 7,7a-dihydro-2(6H)-benzofuranone is prepared by esterification condensation, and then benzofuran-2(3H)-one is obtained by catalytic dehydrogenation. The raw materials of this route are cheap and easy to obtain, the operation is simple, and it has practical application value. Since the condensation reaction is easy to carry out and easy to control, the catalytic dehydrogenation reaction becomes the key to this method. Chinese patent CN 9510710.X discloses a method for preparing benzofuran-2(3H)-one from dihydroxyacetic acid and cyclohexanone. First, dihydroxyacetic acid and cyclohexanone react to form a (2-oxy-cyclohexylidene)acetic acid mixture (including different stereoisomers and γ-lactone forms), and then benzofuran-2(3H)-one is obtained by dehydrogenation. Chinese patent CN 97114606.3 discloses a method for producing a pure 2-oxocyclohexylideneacetic acid enol lactone compound (7,7a-dihydro-2(6H)-benzofuranone) in high yield from dihydroxyacetic acid and cyclohexanone in a pure acetic acid medium, and then synthesizing benzofuran-2(3H)-one at a reaction temperature of 250°C under the action of a Pd / Al2O3 dehydrogenation catalyst. However, the catalyst has poor stability and is easily deactivated.
[0005] In recent years, studies have found that transition metal phosphides have become a hot topic in the research of new hydrogenation catalysts due to their high hydrodesulfurization and hydrodenitrogenation activities. Among them, Ni2P has attracted extensive attention due to its excellent precious metal-like properties. It not only has good resistance to carbon deposition and poisoning, but also has high hydrogenation activity. Since hydrogenation and dehydrogenation are the same reaction center, Ni2P can also show good dehydrogenation performance. Since precious metal catalysts are too expensive, resources are limited, and catalysts are prone to carbon deposition, the development of an efficient dehydrogenation catalyst to replace precious metals is of great significance for industrial applications. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a non-precious metal dehydrogenation catalyst in view of the above-mentioned deficiencies in the prior art. The catalyst is applied to the reaction of catalytic dehydrogenation of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one, while ensuring a high conversion rate and selectivity and having a long service life.
[0007]
[0008] The object of the present invention can be achieved by the following technical scheme: a preparation method of a Ni2P / NiAl2O4 dehydrogenation catalyst, characterized in that nickel aluminum spinel is used as a carrier and Ni2P in a transition metal phosphide is used as an active component, wherein the mass of the active component accounts for 1 to 30% of the total mass of the Ni2P / NiAl2O4 catalyst, preferably 2 to 25%, and more preferably 5 to 20%.
[0009] The dehydrogenation catalyst is prepared by using nickel aluminum spinel as a carrier according to the following steps:
[0010] (1) preparing a mixed solution of nickel salt and aluminum salt, wherein the molar ratio of nickel ion to aluminum ion is 1:2;
[0011] (2) adding the precipitant solution dropwise to the mixed solution prepared in step (1) at a temperature of 30 to 90° C., preferably 35 to 85° C., more preferably 40 to 80° C., with vigorous stirring;
[0012] (3) When the pH value of the precipitation system solution reaches 7 to 13, preferably 8 to 12, and more preferably 9 to 10, the dropwise addition is stopped and the precipitation is aged for 2 to 4 hours;
[0013] (4) Filter and wash the precipitate, dry the filter cake at 100-120° C. for 2-20 h, preferably 4-16 h, more preferably 8-14 h, and calcine it in a muffle furnace at 600-1000° C., preferably 700-900° C., more preferably 750-850° C., for 4-10 h, preferably 5-9 h, more preferably 6-8 h to obtain a nickel-aluminum spinel carrier.
[0014] The precipitant is selected from one of NaOH, Na2CO3, KOH, K2CO3 or a mixture of several thereof, with a mass concentration of 2-30wt%, preferably 5-25wt%, more preferably 8-20wt%.
[0015] The nickel salt is one or more of nickel nitrate, nickel chloride, nickel sulfate or nickel acetate; the aluminum salt is one or more of aluminum nitrate, aluminum chloride or aluminum sulfate. The molar concentration of nickel ions in the mixed solution is 0.05 to 0.65 mol / L, preferably 0.15 to 0.55 mol / L, and more preferably 0.25 to 0.45 mol / L.
[0016] The present invention provides a method for preparing a Ni2P / NiAl2O4 dehydrogenation catalyst, which is prepared according to the following steps:
[0017] (1) dissolving nickel salt and phosphate salt in water, wherein the molar ratio of nickel ion to phosphate ion is 2:1, to form an impregnation solution;
[0018] (2) adding the nickel aluminum spinel support into the impregnation solution, and drying at 60-100° C. for 12 h;
[0019] (3) calcining at 5-500° C., preferably 100-400° C., more preferably 200-300° C., under nitrogen for 1-10 h, then reducing at 100-800° C., preferably 200-700° C., more preferably 400-600° C., under hydrogen for 1-10 h, cooling to room temperature, and passivating under nitrogen for 1-10 h to obtain a Ni2P / NiAl2O4 dehydrogenation catalyst.
[0020] The phosphate salt is diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium hypophosphite, potassium hypophosphite or ammonium hypophosphite, and the mass concentration of the phosphate salt in water is 0.5-30wt%, preferably 1-20wt%, and more preferably 2-15wt%.
[0021] The dehydrogenation catalyst is used in catalyzing the dehydrogenation reaction of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one.
[0022] The catalyst is used to prepare benzofuran-2(3H)-one by dehydrogenation reaction with 7,7a-dihydro-2(6H)-benzofuranone as raw material, and the process conditions are: the reaction is carried out in a trickle bed reactor, the reaction temperature is 50-400°C, preferably 100-300°C, more preferably 120-180°C, and the liquid hourly space velocity is 0.1-10.0h -1 , preferably 0.2~8.0h -1 , more preferably 0.5 to 4.0 h -1 , the reaction pressure is normal pressure, and the nitrogen space velocity is 500~5000h -1 , preferably 1000~4000h -1 , more preferably 2000 to 3000 hours -1 .
[0023] The catalyst is used, and before the reaction, the catalyst is reduced with hydrogen: normal pressure, 150-300° C., pure hydrogen, and reduced for 2-6 hours.
[0024] Compared with the prior art, the advantages of the present invention are:
[0025] (1) The present invention uses nickel aluminum spinel as a carrier, which has better thermal stability, mechanical strength and anti-coking performance than traditional alumina carriers. Since the surface of alumina has strong acidic active centers, it is easy to produce carbon deposits during the dehydrogenation reaction. The nickel aluminum spinel composite metal oxide reduces the acidity of the surface of the alumina carrier, improves the anti-coking ability of the dehydrogenation catalyst, and thus improves the stability of the catalyst.
[0026] (2) The dehydrogenation catalyst disclosed in the present invention uses Ni2P in transition metal phosphide as the dehydrogenation active component, and the cost of the catalyst is much lower than that of existing noble metal dehydrogenation catalysts such as Pd / Al2O3. In addition, the Ni2P active component obtained by the programmed temperature reduction reaction has high dispersibility, thereby improving the dehydrogenation activity and selectivity of the catalyst. At the same time, the synergistic effect between Ni2P and NiAl2O4 can effectively improve and enhance the stability of the catalyst, and achieve good results in the reaction of catalytic dehydrogenation of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD spectra of the nickel aluminum spinel carrier, the supported Ni2P / NiAl2O4 dehydrogenation catalyst and alumina in Example 1;
[0028] Figure 2 The experimental result diagram of the conversion rate of Example 1 and Comparative Example 1 (Comparative Example 1) after the reaction was carried out for 20 hours;
[0029] Figure 3 This is a graph showing the selectivity experimental results of Example 1 and Comparative Example 1 (Comparative Example 1) after the reaction was carried out for 20 hours. DETAILED DESCRIPTION
[0030] The present invention will be further described below with examples. However, the scope of the present invention is not limited by these examples.
[0031] Example 1
[0032] a. Preparation of nickel aluminum spinel support
[0033] (1) 40 g of nickel nitrate, 103.2 g of aluminum nitrate and 400 ml of deionized water were mixed to prepare a mixed solution;
[0034] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at 60° C. with stirring;
[0035] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0036] (4) The precipitate is filtered, washed, and the filter cake is dried at 120° C. for 12 h, and calcined at 800° C. for 6 h to allow nickel oxide and aluminum oxide to undergo a solid phase reaction to obtain a nickel aluminum spinel carrier. Figure 1 The XRD spectra of the nickel aluminum spinel carrier and high temperature calcined alumina (calcined at 800℃ for 6h) are given. The characteristic diffraction peaks of alumina appear at 2θ=37°, 45.1° and 65.7°, while after the catalyst precursor is calcined at high temperature, stronger diffraction peaks appear at 2θ=37°, 45.1° and 65.7°, which are the characteristic peaks of NiAl2O4 spinel, and no diffraction peaks of NiO appear, indicating that Ni atoms completely enter the vacant tetrahedron and octahedron voids in the alumina lattice to form a stable Ni-Al-O spinel structure. The carrier is numbered NiAl2O4-1.
[0037] b. Preparation of 5% Ni2P / NiAl2O4 dehydrogenation catalyst
[0038] 4.13 g of nickel nitrate and 0.94 g of diammonium hydrogen phosphate were dissolved in 20 ml of deionized water to form an impregnation solution; 20 g of nickel aluminum spinel carrier (numbered NiAl2O4-1) was added to the impregnation solution and impregnated at room temperature for 2 h; the resulting product was dried at 80°C for 10 h, calcined at 250°C for 2 h under nitrogen, reduced at 500°C for 2 h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 h to obtain a 5% Ni2P / NiAl2O4 catalyst (wherein 5% represents that the mass of the active component Ni2P accounts for 5% of the total mass of the Ni2P / NiAl2O4 catalyst, the same below). Figure 1 The XRD spectrum of the 5% Ni2P / NiAl2O4 catalyst is also given, and the characteristic diffraction peaks of Ni2P appear at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides are detected in the figure. The catalyst number is CAT-1.
[0039] Example 2
[0040] a. Preparation of nickel aluminum spinel support
[0041] (1) 40 g of nickel nitrate, 103.2 g of aluminum nitrate and 400 ml of deionized water were mixed to prepare a mixed solution;
[0042] (2) adding 15 wt % sodium carbonate solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0043] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 2 hours;
[0044] (4) The precipitate was filtered and washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to cause a solid phase reaction between nickel oxide and aluminum oxide to obtain a nickel aluminum spinel carrier. XRD analysis showed that strong diffraction peaks appeared at 2θ=37°, 45.1° and 65.7°, which were characteristic peaks of the NiAl2O4 spinel structure, and no diffraction peaks of NiO appeared. The carrier was numbered NiAl2O4-2.
[0045] b. Preparation of 10% Ni2P / NiAl2O4 dehydrogenation catalyst
[0046] 8.72g of nickel nitrate and 2.12g of disodium hydrogen phosphate were dissolved in 30ml of deionized water to form an impregnation solution; 20g of nickel aluminum spinel carrier (numbered NiAl2O4-2) was added to the impregnation solution and impregnated at room temperature for 2h; the obtained product was dried at 80℃ for 10h, calcined at 250℃ for 2h under nitrogen, reduced at 500℃ for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 10% Ni2P / NiAl2O4 catalyst. After XRD analysis, the diffraction peaks of Ni2P appeared at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides were detected. The catalyst number is CAT-2.
[0047] Example 3
[0048] a. Preparation of nickel aluminum spinel support
[0049] (1) 40 g of nickel nitrate, 103.2 g of aluminum nitrate and 400 ml of deionized water were mixed to prepare a mixed solution;
[0050] (2) adding 10 wt % potassium hydroxide solution dropwise to the mixed solution prepared in step (1) at 90° C. with stirring;
[0051] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 90°C, and age the precipitate for 2 hours;
[0052] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours, and calcined at 800°C for 6 hours to allow nickel oxide and aluminum oxide to react in a solid phase to obtain a nickel aluminum spinel carrier. XRD analysis showed that strong diffraction peaks appeared at 2θ=37°, 45.1° and 65.7°, which are characteristic peaks of the NiAl2O4 spinel structure, and no diffraction peaks of NiO appeared. The carrier was numbered NiAl2O4-3.
[0053] b. Preparation of 15% Ni2P / NiAl2O4 dehydrogenation catalyst
[0054] 13.84g nickel nitrate and 2.09g sodium hypophosphite were dissolved in 40ml deionized water to form an impregnation solution; 20g nickel aluminum spinel carrier (numbered NiAl2O4-3) was added to the impregnation solution and impregnated at room temperature for 2h; the obtained product was dried at 80℃ for 10h, calcined at 250℃ for 2h under nitrogen, reduced at 550℃ for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 15% Ni2P / NiAl2O4 catalyst. After XRD analysis, the diffraction peaks of Ni2P appeared at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides were detected. The catalyst number is CAT-3.
[0055] Example 4
[0056] a. Preparation of nickel aluminum spinel support
[0057] (1) 40 g of nickel nitrate, 103.2 g of aluminum nitrate and 400 ml of deionized water were mixed to prepare a mixed solution;
[0058] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at a temperature of 40° C. and stirring;
[0059] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 40°C, and age the precipitate for 2 hours;
[0060] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours, and calcined at 900°C for 6 hours to cause a solid phase reaction between nickel oxide and aluminum oxide to obtain a nickel aluminum spinel carrier. XRD analysis showed that strong diffraction peaks appeared at 2θ=37°, 45.1° and 65.7°, which are characteristic peaks of the NiAl2O4 spinel structure, and no diffraction peaks of NiO appeared. The carrier was numbered NiAl2O4-4.
[0061] b. Preparation of 20% Ni2P / NiAl2O4 dehydrogenation catalyst
[0062] 19.6g nickel nitrate and 2.9g sodium hypophosphite were dissolved in 40ml deionized water to form an impregnation solution; 20g nickel aluminum spinel carrier (numbered NiAl2O4-4) was added to the impregnation solution and impregnated at room temperature for 2h; the obtained product was dried at 80℃ for 10h, calcined at 250℃ for 2h under nitrogen, reduced at 550℃ for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 20% Ni2P / NiAl2O4 catalyst. After XRD analysis, the diffraction peaks of Ni2P appeared at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides were detected. The catalyst number is CAT-4.
[0063] Example 5
[0064] a. Preparation of nickel aluminum spinel support
[0065] (1) 35.6 g of nickel chloride, 71.9 g of aluminum chloride and 200 ml of deionized water were mixed to prepare a mixed solution;
[0066] (2) adding 15 wt % sodium carbonate solution dropwise to the mixed solution prepared in step (1) at 60° C. with stirring;
[0067] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0068] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours, and calcined at 800°C for 6 hours to allow nickel oxide and aluminum oxide to react in a solid phase to obtain a nickel aluminum spinel carrier. XRD analysis showed that strong diffraction peaks appeared at 2θ=37°, 45.1° and 65.7°, which are characteristic peaks of the NiAl2O4 spinel structure, and no diffraction peaks of NiO appeared. The carrier was numbered NiAl2O4-5.
[0069] b. Preparation of 10% Ni2P / NiAl2O4 dehydrogenation catalyst
[0070] 7.1g nickel chloride and 1.98g diammonium hydrogen phosphate were dissolved in 20ml deionized water to form an impregnation solution; 20g nickel aluminum spinel carrier (numbered NiAl2O4-5) was added to the impregnation solution and impregnated at room temperature for 2h; the obtained product was dried at 80℃ for 10h, calcined at 300℃ for 2h under nitrogen, reduced at 600℃ for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 10% Ni2P / NiAl2O4 catalyst. After XRD analysis, the diffraction peaks of Ni2P appeared at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides were detected. The catalyst number is CAT-5.
[0071] Example 6
[0072] a. Preparation of nickel aluminum spinel support
[0073] (1) 26.9 g of nickel acetate, 73.4 g of aluminum chloride and 200 ml of deionized water were mixed to prepare a mixed solution;
[0074] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0075] (3) When the pH value of the solution reaches 8, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 2 hours;
[0076] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours, and calcined at 900°C for 6 hours to allow nickel oxide and aluminum oxide to react in a solid phase to obtain a nickel aluminum spinel carrier. XRD analysis showed that strong diffraction peaks appeared at 2θ=37°, 45.1° and 65.7°, which are characteristic peaks of the NiAl2O4 spinel structure, and no diffraction peaks of NiO appeared. The carrier was numbered NiAl2O4-6.
[0077] b. Preparation of 10% Ni2P / NiAl2O4 dehydrogenation catalyst
[0078] 5.29g of nickel acetate and 1.24g of ammonium hypophosphite were dissolved in 20ml of deionized water to form an impregnation solution; 20g of nickel aluminum spinel carrier (numbered NiAl2O4-6) was added to the impregnation solution and impregnated at room temperature for 2h; the obtained product was dried at 100℃ for 10h, calcined at 300℃ for 2h under nitrogen, reduced at 600℃ for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 10% Ni2P / NiAl2O4 catalyst. After XRD analysis, the diffraction peaks of Ni2P appeared at 2θ=40.5°, 44.8° and 47.5°, and no other metal phosphides were detected. The catalyst number is CAT-6.
[0079] Comparative Example 1
[0080] Using alumina as a carrier (pre-calcined at 800°C for 6h), weigh 0.251g of a 20wt% H2PdCl4 aqueous solution containing Pd and add 10ml of deionized water to fully dissolve it. Then, 10g of high-temperature treated alumina is immersed in the solution, naturally dried in the shade, dried at 120°C for 12h, and calcined at 400°C for 4h to obtain a 0.5% Pd / Al2O3 catalyst.
[0081] Example 7
[0082] The reaction performance of the catalysts prepared in Examples 1-6 and Comparative Example 1 in the catalytic dehydrogenation of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one was evaluated using a trickle bed reactor.
[0083] Evaluation method: The reaction tube is a 316L stainless steel tube with an inner diameter of 9 mm. The catalyst is tableted, crushed and sieved to 20-40 mesh. The filling amount is 4 ml and placed in the constant temperature zone in the middle of the reactor. An appropriate amount of 20-40 mesh inert quartz sand is loaded above and below the bed.
[0084] Catalyst reduction: atmospheric pressure, 250°C, pure hydrogen, space velocity 1000h -1 , reduction for 4h;
[0085] Then the temperature was lowered to 160°C and 7,7a-dihydro-2(6H)-benzofuranone was pumped into the reactor at normal pressure and a liquid hourly space velocity of 2.0 h -1 , N2 airspeed 2500h -1The dehydrogenation reaction was carried out under the following conditions. The product was analyzed by an Agilent 7890 gas chromatograph equipped with an HP-5 capillary column and an FID detector. The conversion rate of the raw material and the selectivity of the product were calculated by the area normalization method. The experimental results are shown in Table 1. It can be found from Table 1 that the dehydrogenation catalysts prepared in Examples 1 to 6 show high reaction activity and selectivity in the reaction system of catalytic dehydrogenation of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one. The conversion rates of 7,7a-dihydro-2(6H)-benzofuranone were all greater than 60%, and the selectivity of benzofuran-2(3H)-one was all above 93%.
[0086] In order to illustrate that the dehydrogenation catalyst provided by the present invention has better stability, the inventors conducted a 20-hour stability test on the catalysts prepared in Example 1 and Comparative Example 1 (Comparative Example 1). The experimental results are shown in FIG. Figure 2 and Figure 3 . The alumina-supported Pd catalyst given in Comparative Example 1 showed high activity and selectivity in the first 2 hours of the reaction, but the catalyst activity and selectivity decreased rapidly with the reaction time. The conversion rate of 7,7a-dihydro-2(6H)-benzofuranone and the selectivity of benzofuran-2(3H)-one were 67.4% and 90.7% in the initial 2 hours of the reaction, and dropped to 55.3% and 82.3% respectively after 20 hours of reaction. The 10% Ni2P / NiAl2O4 catalyst given in Example 2 had a conversion rate of 64.8% and a selectivity of 94.7% after 2 hours of reaction. After 20 hours of reaction, the conversion rate and selectivity were 63.8% and 92.2% respectively, and the dehydrogenation activity and selectivity did not decrease significantly. It can be seen that the dehydrogenation reaction performance of the nickel aluminum spinel-supported Ni2P catalyst is significantly better than that of the Pd / Al2O3 catalyst.
[0087] Table 1 Dehydrogenation performance of different catalysts
[0088]
[0089] Reaction conditions: temperature 160°C, normal pressure, liquid hourly space velocity 2.0h -1 , N2 airspeed 2500h -1 , sampling time 2h.
Claims
1. A NiAl2O4-supported Ni2P dehydrogenation catalyst, characterized in that: Nickel aluminum spinel is used as a carrier and transition metal phosphide Ni2P is used as an active component, wherein the mass of the active component accounts for 1-30% of the total mass of the Ni2P / NiAl2O4 catalyst, preferably 2-25%, and more preferably 5-20%.
2. The dehydrogenation catalyst according to claim 1, characterized in that The nickel aluminum spinel carrier is prepared by the following method: (1) preparing a mixed solution of nickel salt and aluminum salt, wherein the molar ratio of nickel ion to aluminum ion is 1:2, and adding the precipitant solution dropwise to the mixed solution prepared in step (1) under stirring at a temperature of 30 to 90° C., preferably 35 to 85° C., and more preferably 40 to 80° C.; (3) When the pH value of the precipitation system solution reaches 7 to 13, preferably 8 to 12, and more preferably 9 to 10, the dropwise addition is stopped and the precipitation is aged for 2 to 4 hours; (4) Filter and wash the precipitate, dry the filter cake at 100-120° C. for 2-20 h, preferably 4-16 h, more preferably 8-14 h, and calcine in a muffle furnace at 600-1000° C., preferably 700-900° C., more preferably 750-850° C., for 4-10 h, preferably 5-9 h, more preferably 6-8 h to obtain a nickel-aluminum spinel carrier.
3. The preparation method according to claim 2, characterized in that: The precipitant is selected from one of NaOH, Na2CO3, KOH, K2CO3 or a mixture of two or more thereof, with a mass concentration of 2-30%, preferably 5-25%, and more preferably 8-20%.
4. The preparation method according to claim 2, characterized in that: The nickel salt is one or more of nickel nitrate, nickel chloride, nickel sulfate or nickel acetate; the aluminum salt is one or more of aluminum nitrate, aluminum chloride or aluminum sulfate, and the molar concentration of nickel ions in the mixed solution is 0.05-0.65 mol / L, preferably 0.15-0.55 mol / L, and more preferably 0.25-0.45 mol / L.
5. A method for preparing the dehydrogenation catalyst according to claim 1, characterized in that: The Ni2P / NiAl2O4 catalyst is prepared by the following method: (1) dissolving nickel salt and phosphate salt in water, wherein the molar ratio of nickel ion to phosphate ion is 2:1, to form an impregnation solution; (2) adding the nickel aluminum spinel support into the impregnation solution, and drying at 60 to 80° C. for 8 to 20 hours; (3) calcining at 50-500° C., preferably 100-400° C., more preferably 200-300° C., under nitrogen for 1-10 h, then reducing at 100-800° C., preferably 200-700° C., more preferably 400-600° C., under hydrogen for 1-10 h, cooling to room temperature, and passivating under nitrogen for 1-10 h to obtain a Ni2P / NiAl2O4 dehydrogenation catalyst.
6. The preparation method according to claim 5, characterized in that: The phosphate salt is one or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium hypophosphite, potassium hypophosphite or ammonium hypophosphite; the mass concentration of the phosphate salt in water is 0.5-30%, preferably 1-20%, more preferably 2-15%.
7. Use of the dehydrogenation catalyst according to any one of claims 1 to 4 in catalyzing the dehydrogenation reaction of 7,7a-dihydro-2(6H)-benzofuranone to prepare benzofuran-2(3H)-one.
8. The use according to claim 7, characterized in that: 7,7a-dihydro-2(6H)-benzofuranone is used as a raw material to prepare benzofuran-2(3H)-one through a dehydrogenation reaction, wherein the process conditions are as follows: the reaction is carried out in a trickle bed reactor, the reaction temperature is 50 to 400° C. (preferably 100 to 300° C., more preferably 120 to 180° C., and the liquid hourly space velocity is 0.1 to 10.0 h -1 , preferably 0.2~8.0h -1 , more preferably 0.5 to 4.0 h -1 , the reaction pressure is normal pressure, and the nitrogen space velocity is 500~5000h -1 , preferably 1000~4000h -1 , more preferably 2000 to 3000 hours -1 .
9. The use according to claim 8, characterized in that: The catalyst is reduced with hydrogen before the reaction: Normal pressure, 150-300°C, pure hydrogen, reduction for 2-6 hours.
Citation Information
Patent Citations
Method for synthesizing 2(3H)-benzofuranone by utilizing microwave
CN102887879A
Preparation method of benzofuranone
CN111057031A
Preparation process for 2-oxocyclohexylidene acetate enol-lacton and application thereof
CN1185436A
Process for the preparation of pyrimidine compounds
WO1992008703A1
Cited By
Method for catalytic cracking of composite insulator glass fiber core rod
CN120421316A
